Advanced cardiac chemical exchange saturation transfer (cardioCEST) MRI for in vivo cell tracking and metabolic imaging. (January 2016) - Pumphrey, Ashley; Yang, Zhengshi; Ye, Shaojing; Powell, David K.; Thalman, Scott; Watt, David S.; Abdel‐Latif, Ahmed; Unrine, Jason; Thompson, Katherine; Fornwalt, Brandon; Ferrauto, Giuseppe; Vandsburger, Moriel
Abstract : An improved pre‐clinical cardiac chemical exchange saturation transfer (CEST) pulse sequence (cardioCEST) was used to selectively visualize paramagnetic CEST (paraCEST)‐labeled cells following intramyocardial implantation. In addition, cardioCEST was used to examine the effect of diet‐induced obesity upon myocardial creatine CEST contrast. CEST pulse sequences were designed from standard turbo‐spin‐echo and gradient‐echo sequences, and a cardiorespiratory‐gated steady‐state cine gradient‐echo sequence. In vitro validation studies performed in phantoms composed of 20 mM Eu‐HPDO3A, 20 mM Yb‐HPDO3A, or saline demonstrated similar CEST contrast by spin‐echo and gradient‐echo pulse sequences. Skeletal myoblast cells (C2C12) were labeled with either Eu‐HPDO3A or saline using a hypotonic swelling procedure and implanted into the myocardium of C57B6/J mice. Inductively coupled plasma mass spectrometry confirmed cellular levels of Eu of 2.1 × 10 −3 ng/cell in Eu‐HPDO3A‐labeled cells and 2.3 × 10 −5 ng/cell in saline‐labeled cells. In vivo cardioCEST imaging of labeled cells at ±15 ppm was performed 24 h after implantation and revealed significantly elevated asymmetric magnetization transfer ratio values in regions of Eu‐HPDO3A‐labeled cells when compared with surrounding myocardium or saline‐labeled cells. We further utilized the cardioCEST pulse sequence to examine changes in myocardial creatine in response to diet‐induced obesity by acquiring pairs of cardioCEST images at ±1.8 ppm. While ventricular geometry and function were unchanged between mice fed either a high‐fat diet or a corresponding control low‐fat diet for 14 weeks, myocardial creatine CEST contrast was significantly reduced in mice fed the high‐fat diet. The selective visualization of paraCEST‐labeled cells using cardioCEST imaging can enable investigation of cell fate processes in cardioregenerative medicine, or multiplex imaging of cell survival with imaging of cardiac structure and function and additional imaging of myocardial creatine. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this study we designed and validated an improved cardiac chemical exchange saturation transfer (cardioCEST) pulse sequence. Application of this sequence to CEST‐based cell tracking following intramyocardial cell transplantation demonstrated excellent detection of Eu‐HPDO3A‐labeled cells. Additional application to creatine imaging identified reduced myocardial creatine contrast as an early marker of cardiac dysfunction in diet‐induced obesity.